Implementation Of Legal Protection Of Children As Victims Of Domestic Psychic Violence - Dwi Kurniawan (Jurnal Daulat Hukum, 2018)
This research is focused on the normative legal norms and also the object of the law as the main data, they get out of control and a book of rules, which should be fine correctness of the research that has been done. The author conducted research in the area of Semarang Polrestabes. The results of this study are: (1) Implementation of the legal protection of children as victims of domestic violence can be done in two ways, namely the vicissitudes of non-penal and penal. Non-penal efforts undertaken by preemptive and preventive, while the penal effort is an attempt by the police as repressive as psychological violence in the domestic sphere occurred and reported to the police; (2) Constraints faced by the police in the implementation of the legal protection of children as victims of psychological violence in the household, namely: (a) Difficulty in finding strong evidence of child victims of psychological violence, in this case the question is about how to form psychological violence. (B) The difficulty to distinguish children who suffered emotional abuse committed by family members in a household setting. A child who is exposed to violence usually have a psychological fear to reveal their problems as a result of the perpetrator's actions. (C) The number of child victims of psychological violence for people who shut themselves in their environment and also included the police or Child Protective Services. (D) delay in reporting of family members in the household,Keywords: Legal Protection, Child, Domestic Violence.